Case for diagnosis - Camila Bueno Requena; Hélio Amante Miot; Mariângela Esther Alencar Marques; Luciane Donida Bartoli Miot (Sociedade Brasileira de Dermatologia, 2014)
Pachydermodactyly is a rare and benign form of acquired digital fibromatosis characterized by the expansion of soft tissue around proximal phalanges and interphalangeal joints. The etiology remains unknown, although it is suggested that repetitive mechanic trauma like the interlacing or rubbing of the fingers can lead to skin thickening. We report a case of a young man with skin thickening around interphalangeal joints and compulsive finger manipulation habit. The histopathology disclosed hyperkeratosis, discrete papillomatosis, mild increase of fibroblasts and dermal mucinosis. The lesions regressed partially, after finger manipulation was stopped.